Smart Power Potential of the EU: Example of the Operation EUFOR Althea in Bosnia and Herzegovina - Emine Akçadağ Alagöz (Ankara Avrupa Çalışmaları Dergisi)
Despite growing interest in the concept of smart power, scholarly works on the substance and definition of this concept are always limited. In this paper, the EU’s exercise of smart power will be analyzed through the EU’s comprehensive approach in crisis management, using the EUFOR Althea operation as a case study. The objective of this paper is to demonstrate the EU’s smart power potential and contribute to a better understanding of the concept of smart power which is still in the nascent state